Механiзми еволюцiї поверхнi при ростi нелегованих нанокремнiєвих плiвок - Nakhodkin, N. G.; Rodionova, T. V.; Sutyagina, A. S. (Publishing house "Academperiodika", 2019)
The thickness dependence of the surface roughness and the grain size of nanosilicon films, produced by low-pressure chemical vapour deposition, has been found, by using atomic force microscopy. A correlation between the surface roughness, grain size, and transformation of a film structure from the equiaxial structure into a fibrous one is established. Possible mechanisms of surface evolution are analyzed.